Low-dose radiation ameliorates PM2.5-induced lung injury through non-canonical TLR1/TLR2-like receptor pathways modulated by Akkermansia muciniphila - Li Wang; Zhipeng Li; Huan He; Lijing Qin; Weiqiang Xu; Hongyuan Tian; Rongrong Liu; Xinru Lian; Wen Li; Yali Qi; Zhicheng Wang (Ecotoxicology and Environmental Safety)
Exposure of PM2.5 can cause different degrees of lung injury, which is referred with inflammatory response. Some evidences showed that low-dose radiation (LDR) induces hormesis in immune, however, it is unknown if LDR ameliorates the PM2.5-induced lung injury. Additionally, gut microbiota and inflammation are crucial in lung injury and the health benefits of LDR through gut microbiota need further exploration. Here, we aim to investigate the impact of LDR on PM2.5-induced lung injury in vivo and in vitro, and elucidated the potential mechanisms of anti-inflammation activated by gut microbiota. We observed that LDR ameliorated the lung damage induced by PM2.5 in mice. Additionally, after PM2.5 exposure, M1 polarization of macrophages in alveolar lavage fluid and Th1 polarization in spleen increased, pro-inflammatory cytokines (IL-1, IL-6 and TNF-α) increased and anti-inflammatory cytokines (IL-4, IL-10 and TGF-β) decreased in lung and serum. LDR could deteriorate the changes described as above. Intriguingly, Akkermansia muciniphila (Akk) differed most significantly in the gut microbiota of mice. Notably, PM2.5 activated the Toll-like receptors-induced MyD88/NF-κB pathways to mediate the pro-inflammation, and LDR could inhibited the pathway. However, the TLR1 and TLR2 continuously increased after LDR, indicating the downstream non-canonical TLR1/TLR2 pathway of Akk was activated to blunt the pro-inflammation of PM2.5. Our results strongly indicate that LDR-induced activation of gut Akk-dependent non-canonical TLR1/TLR2-like receptor pathway ameliorates lung injury and inflammation resulted from PM2.5.